Prediction of Net Profit Growth of Pharmacy Companies on the Indonesian Stock Exchange - Dhani Ichsanuddin Nur (Shahid Sadoughi University of Medical Sciences, 2019)
Background: The research purpose to analyzing impacts of funding source changes on pharmacy company profits that went public on Indonesian Stock Exchange, with analysis period of 2008 to 2013. Methods: The research applied analysis means in line with requirements of change variable measurements of funding sources in its interconnectedness with company profits; the applied model was Auto-regressive. Results: The research results indicated that changes of the last one-period short term debts had negative effects insignificantly on company profits, the last two-period short term debts had positive effects significantly on company profits, changes of the last one-period and two-period long term debts had negative effects insignificantly on company profits, equity changes of the last period had positive effects significantly on company profits, the last period profit changes had negative effects significantly on company profits. Conclusion: Last one-period short term, last one-period long term, last two-period long term debt changes, and last period profit have negative insignificant effect on company profit. Last two-period short term debt changes, last one-period equity changes, and last two-period equity changes have positive significant effect on company profit.